Chapter Ultrafast Time‐Resolved Measurements of Hybrid Solar Cells - Zheng, Kaibo (InTechOpen, 2017)
The early time charge carrier dynamics in quantum dot‐sensitized and organo‐metal halide perovskite solar cells are presented in this chapter. Using transient spectroscopy techniques, i.e., absorption, photoluminescence, and photoconductivity, we probed the generation mechanism, charge injection, mobility, and recombination of charges in the time scales of subpicosecond (ps) to a nanosecond. In few ps, electron injection from quantum dot to n‐type metal oxide (MO) is complete while hole injection to p‐type MO required hundreds of ps. The injection process is dictated by the band alignment, density of states of MO and the charge transfer state at the interface. For organo‐metal halide perovskite material, there is a distribution of exciton binding energy brought about by the nonuniformity in the quality of the sample. As a result, varying amount of exciton and highly mobile charges may be generated depending on the morphology of the film. In the sample presented here, we found that 30% of photo‐generated charges are excitons, which then dissociates within 2-3 ps. The rest of the photons are instantaneously converted into highly mobile charges (µe = 12.5 cm2 V-1 s-1 and µh = 7.5 cm2 V-1 s-1), and at the appropriate excitation fluence, the photoconductivity remains constant up to 1 ns. The time scale and mechanism of charge injection from perovskite into organic electrodes are also presented.